Analisis Perbandingan Produktivitas dan Value Engineering pada Pelaksanaan Pekerjaan Pemasangan Bata Merah dan Bata Ringan: (Studi Kasus : Proyek Perumahan Shopee Semanggi) - Ivan Fadhila; Ary Setyawan; Koosdaryani Soeryodarundio (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The selection of building materials is vital for the development of high-quality infrastructure and residential projects. The two most commonly used building materials are red bricks and lightweight bricks. This study compares the productivity and cost of red brick and lightweight brick production and installation in construction projects. Data were obtained through direct observation, worker interviews, and Value Engineering analysis on the Shopee Semanggi Housing Project, which consists of 136 houses with a total estimated budget (RAB) of Rp10.93 billion. The results show that red brick installation productivity is 3.3 m²/day, while lightweight brick installation reaches 17.9 m²/day. The installation cost for red bricks is Rp1.52 billion for 12,786.78 m², compared to Rp1.62 billion for lightweight bricks for the same area. This study provides guidance for selecting building materials based on time and cost efficiency.